Analyzing Ed-tech industry’s growth opportunity & educational development scope through digital marketing in Bangladesh: a follow up on ‘Innokids’ organization - Islam, Md. Toufiqul (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.